GENETIC DIVERSITY OF M. TUBERCULOSIS IN YAMALO-NENETS AUTONOMOUS DISTRICT - T. V. Umpeleva; K. V. Belousova; L. A. Golubeva; T. Yu. Boteva; N. I. Eremeeva; D. V. Vakhrusheva (Туберкулез и болезни лёгких)
.